Experimental Selves Person and Experience in Early Modern Europe - Braider, Christopher 1950- (University of Toronto Press, 2018)
Drawing on the generous semantic range the term enjoyed in early modern usage, the book argues that person as early moderns understood it was an "experimental" phenomenon--at once a given of experience and the self-conscious arena of that experience.